2008
DOI: 10.1007/s12017-008-8032-3
|View full text |Cite
|
Sign up to set email alerts
|

Neuroplasticity of Dopamine Circuits After Exercise: Implications for Central Fatigue

Abstract: Habitual exercise increases plasticity in a variety of neurotransmitter systems. The current review focuses on the effects of habitual physical activity on monoamine dopamine (DA) neurotransmission and the potential implication of these changes to exercise-induced fatigue. Although it is clear that peripheral adaptations in muscle and energy substrate utilization contribute to this effect, more recently it has been suggested that central nervous system pathways "upstream" of the motor cortex, which initiate ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
194
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(206 citation statements)
references
References 117 publications
(157 reference statements)
10
194
0
2
Order By: Relevance
“…Mechanistically, acute physical exercise activates the dopaminergic reward pathway through increases in dopamine concentrations and dopamine receptor binding (Greenwood et al, 2011). Moreover, chronic voluntary and forced running increases dopamine levels in the brain (Foley and Fleshner, 2008;Greenwood et al, 2011;Sutoo and Akiyama, 1996). The ventral tegmental area shows stronger phasic dopamine spikes after voluntary wheel running in rats (Wang and Tsien, 2011), suggesting that neurons in the ventral tegmental area code motivational signals which trigger, sustain, or end movement.…”
Section: Outlook: Possible New Therapies For Comorbid Obesitymentioning
confidence: 99%
“…Mechanistically, acute physical exercise activates the dopaminergic reward pathway through increases in dopamine concentrations and dopamine receptor binding (Greenwood et al, 2011). Moreover, chronic voluntary and forced running increases dopamine levels in the brain (Foley and Fleshner, 2008;Greenwood et al, 2011;Sutoo and Akiyama, 1996). The ventral tegmental area shows stronger phasic dopamine spikes after voluntary wheel running in rats (Wang and Tsien, 2011), suggesting that neurons in the ventral tegmental area code motivational signals which trigger, sustain, or end movement.…”
Section: Outlook: Possible New Therapies For Comorbid Obesitymentioning
confidence: 99%
“…[21][22][23][24][25][26][27]. Other factors such as electrical stimulation (transcranial direct current stimulation), habitual exercise, pharmacological agents, psycho-/behavioral therapy, stress as well as environmental factors also affect neurometaplasticity [28][29][30][31][32][33][34][35]. These factors affect neurometaplasticity by indirect influence on neurotransmitters, receptors, transporters, genome and epigenome of brain cells [29,30].…”
Section: Mechanisms Of Neurometaplasticitymentioning
confidence: 99%
“…Other factors such as electrical stimulation (transcranial direct current stimulation), habitual exercise, pharmacological agents, psycho-/behavioral therapy, stress as well as environmental factors also affect neurometaplasticity [28][29][30][31][32][33][34][35]. These factors affect neurometaplasticity by indirect influence on neurotransmitters, receptors, transporters, genome and epigenome of brain cells [29,30]. The receptors implicated in LTP and LTD include N-methyl-D-aspartate receptor (NMDAR), metabotropic glutamate receptors (mGluRs), endocannabinoid receptors, ion channel receptors (e.g.…”
Section: Mechanisms Of Neurometaplasticitymentioning
confidence: 99%
“…DA neurotransmitter levels increases in order to improve the performance in the case of amphetamine administration (Borg, Edström, Linderholm, & Marklund, 1972). However, there is evidence that brain dopamine level is similar to the resting condition during fatigue (Foley & Fleshner, 2008) and this creates the possibility that dopamine concentration in various groups differently increases during exercise. For instance, it has been reported that inhibition of DA reuptake, increases the core temperature at the end of exercise, but has no effect on the performance in normothermia (Watson et al, 2005).…”
Section: Neurotransmitters and Central Fatiguementioning
confidence: 99%